Pengaruh Suhu dan Jangka Waktu Pengeringan Chips Ubi Kayu yang di Fermentasi terhadap Karakteristik Tepung Mocaf - Al Haq, Isa Maulana; Hodijat, Asep; Putranto, Kelik (Jurnal Dimamu, 2025)
Mocaf is a flour that can be used as an alternative to wheat flour. Several factors in mocaf processing can produce flour with poor characteristics, ranging from small yields, high moisture content, brownish color and sour aroma. Some of the factors that influence the making of mocaf flour are the temperature and drying time of cassava chips. The purpose of this research is to determine the right temperature and time period in the drying process of cassava chips so as to obtain good mocaf flour characteristics. The research method used was the experimental method using a factorial pattern Randomized Group Design. The treatments consisted of drying temperature (60oC, 70oC and 80oC) as the main factor and drying time (12 hours, 16 hours and 20 hours) as the second factor, each treatment repeated 3 times. The research was conducted at the Chemistry Laboratory and Food Processing Laboratory of Ma'soem University, Sumedang, from March to July 2024. The results showed that the best drying temperature was 80oC which gave a yield of 26.34%, a degree of fineness of 99.89% and a moisture content of 5.09%. The best drying time was 16 hours with a yield of 23.39%, a degree of fineness of 99.69%, a moisture content of 5.93% and a color value of 3.66. There is an interaction between temperature and drying time. The combination of 60oC drying temperature with a period of 20 hours is the best treatment with a yield of 29.05%, a degree of fineness of 99.93% and a moisture content of 5.33%.